Co-occurrence of posttraumatic stress symptoms, pain, and disability 12 months after traumatic injury. (September 2017) - Giummarra, Melita J.; Casey, Sara L.; Devlin, Anna; Ioannou, Liane J.; Gibson, Stephen J.; Georgiou-Karistianis, Nellie; Jennings, Paul A.; Cameron, Peter A.; Ponsford, Jennie
Abstract: Introduction: Chronic pain is common after traumatic injury and frequently co-occurs with posttraumatic stress disorder (PTSD) and PTSD symptoms (PTSS). Objectives: This study sought to understand the association between probable PTSD, PTSS, and pain. Methods: Four hundred thirty-three participants were recruited from the Victorian Orthopaedic Trauma Outcomes Registry and Victorian State Trauma Registry and completed outcome measures. Participants were predominantly male (n = 324, 74.8%) and aged 17-75 years at the time of their injury (M = 44.83 years, SD = 14.16). Participants completed the Posttraumatic Stress Disorder Checklist, Brief Pain Inventory, Pain Catastrophizing Scale, Pain Self-Efficacy Questionnaire, Tampa Scale of Kinesiophobia, EQ-5D-3L and Roland-Morris Disability Questionnaire 12 months after hospitalization for traumatic injury. Data were linked with injury and hospital admission data from the trauma registries. Results: Those who reported having current problems with pain were 3 times more likely to have probable PTSD than those without pain. Canonical correlation showed that pain outcomes (pain severity, interference, catastrophizing, kinesiophobia, self-efficacy, and disability) were associated with all PTSSs, but especially symptoms of cognition and affect, hyperarousal, and avoidance. Posttraumatic stress disorder symptoms, on the contrary, were predominantly associated with high catastrophizing and low self-efficacy. When controlling for demographics, pain and injury severity, depression, and self-efficacy explained the greatest proportion of the total relationship between PTSS and pain-related disability. Conclusion: Persons with both PTSS and chronic pain after injury may need tailored interventions to overcome fear-related beliefs and to increase their perception that they can engage in everyday activities, despite their pain. Abstract : Supplemental Digital Content is Available in the Text.This study showed that PTSD is associated with worse pain and disability at 12 months after traumatic injury. The associations between PTSD criterion symptoms and pain outcomes highlight the likely occurrence of shared mechanisms, particularly between the experience of severe pain, hyperarousal, avoidance, and cognitive appraisals of stress or pain. New efforts are required to develop and validate interventions that can effectively treat comorbid pain and PTSD to prevent their long-term impacts on psychological wellbeing and socioeconomic position.